2018
DOI: 10.1016/j.dib.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome sequences of the oomycete Pythium insidiosum strain CBS 573.85 from a horse with pythiosis and strain CR02 from the environment

Abstract: Pythium insidiosum is an aquatic oomycete microorganism that causes the fatal infectious disease, pythiosis, in humans and animals. The organism has been successfully isolated from the environment worldwide. Diagnosis and treatment of pythiosis is difficult and challenging. Genome sequences of P. insidiosum, isolated from humans, are available and accessible in public databases. To further facilitate biology-, pathogenicity-, and evolution-related genomic and genetic studies of P. insidiosum, we report two add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…The genomic data of P. destruens represent a pathogen strain from the continent of Australia. Bioinformatics and comparative genomics analyses of the pathogen genome data reported by this and other studies [5][6][7][8][9][10] could provide insights into basic biology, genetic variation, host specificity, and underlying pathogenesis mechanism and lead to identifying potential target genes for the development of a novel control measure (i.e., drug and vaccine) against pythiosis.…”
Section: Objectivementioning
confidence: 82%
See 1 more Smart Citation
“…The genomic data of P. destruens represent a pathogen strain from the continent of Australia. Bioinformatics and comparative genomics analyses of the pathogen genome data reported by this and other studies [5][6][7][8][9][10] could provide insights into basic biology, genetic variation, host specificity, and underlying pathogenesis mechanism and lead to identifying potential target genes for the development of a novel control measure (i.e., drug and vaccine) against pythiosis.…”
Section: Objectivementioning
confidence: 82%
“…Detection and management of patients with pythiosis are complicated and problematic in the clinics due to the lack of efficient diagnostic and therapeutic tools, as well as basic knowledge of the disease. Genomes of 6 P. insidiosum strains isolated from different sources (i.e., human, horse, and water) and geographic locations in the continents of Asia and Americas (i.e., the United States, Costa Rica, Brazil, and Thailand) were sequenced and deposited in the public data repositories [5][6][7][8][9][10], and become an invaluable resource for bioinformatics and functional genetic studies of this organism.…”
Section: Objectivementioning
confidence: 99%
“…The urease and urease accessory protein sequences of the plant Arabidopsis thaliana (accession numbers: (urease structure protein, URE); (urease accessory protein D, URED); (urease accessory protein F, UREF); and (urease accessory protein G, UREG)) ( Witte, Rosso & Romeis, 2005 ) were retrieved from the NCBI database. To assess the presence of the orthologs in P. insidiosum , all of these Arabidopsis proteins were TBLASTN searched against the genome of the P. insidiosum strain Pi35 (also known as Pi-S), and two Illumina-derived genomes of the P. insidiosum strains Pi07 (also known as CBS 573.85) and Pi45 ( Rujirawat et al, 2015 ; Kittichotirat et al, 2017 ; Patumcharoenpol et al, 2018 ), using the locally installed blast 2.2.28+ program ( ) and the cut-off E -value ≤10 −6 .…”
Section: Methodsmentioning
confidence: 99%
“…In this sense, the available oomycete genomes are mainly related to plant pathogens, which is a limitation for evolutionary studies . Moreover, when it comes to mammalian pathogens, for example Pythium , there is also a bias towards the number and origin of genome sequences available, both regarding geographic provenance and host …”
Section: Introductionmentioning
confidence: 98%
“…Moreover, when it comes to mammalian pathogens, for example Pythium, there is also a bias towards the number and origin of genome sequences available, both regarding geographic provenance and host. 14,16,17 Genetic studies have subdivided the genus Pythium into 10 distinct clades, named A to J, which include Pythium sensu lato. 8,10 Nevertheless, further phylogenetic analyses suggested that Pythium is a nonmonophyletic group with some species closely related to Peronosporales species.…”
Section: Introductionmentioning
confidence: 99%